Stimulation of chondrogenic differentiation of adult human bone marrow-derived stromal cells by a moderate-strength static magnetic field - Amin,HD; Brady,MA; St-Pierre,J-P; Stevens,MM; Overby,DR; Ethier,CR (Tissue Engineering: Parts A, B, and C, 2014)
Tissue-engineering strategies for the treatment of osteoarthritis would benefit from the ability to induce chondrogenesis in precursor cells. One such cell source is bone marrow-derived stromal cells (BMSCs). Here, we examined the effects of moderate-strength static magnetic fields (SMFs) on chondrogenic differentiation in human BMSCs in vitro. Cells were cultured in pellet form and exposed to several strengths of SMFs for various durations. mRNA transcript levels of the early chondrogenic transcription factor SOX9 and the late marker genes ACAN and COL2A1 were determined by reverse transcription–polymerase chain reaction, and production of the cartilage-specific macromolecules sGAG, collage type 2 (Col2), and proteoglycans was determined both biochemically and histologically. The role of the transforming growth factor (TGF)-β signaling pathway was also examined. Results showed that a 0.4 T magnetic field applied for 14 days elicited a strong chondrogenic differentiation response in cultured BMSCs, so long as TGF-β3 was also present, that is, a synergistic response of a SMF and TGF-β3 on BMSC chondrogenic differentiation was observed. Further, SMF alone caused TGF-β secretion in culture, and the effects of SMF could be abrogated by the TGF-β receptor blocker SB-431542. These data show that moderate-strength magnetic fields can induce chondrogenesis in BMSCs through a TGF-β-dependent pathway. This finding has potentially important applications in cartilage tissue-engineering strategies.